2019 Diagnostic criteria for mixed connective tissue disease (MCTD): From the Japan research committee of the ministry of health, labor, and welfare for systemic autoimmune diseases. Issue 1 (2nd January 2021) - Tanaka, Yoshiya; Kuwana, Masataka; Fujii, Takao; Kameda, Hideto; Muro, Yoshinao; Fujio, Keishi; Itoh, Yasuhiko; Yasuoka, Hidekata; Fukaya, Shusaku; Ashihara, Konomi; Hirano, Daisuke; Ohmura, Koichiro; et al.
Abstract: Objective: To update and revise the diagnostic criteria for mixed connective tissue disease (MCTD) issued by the Japan Research Committee of the Ministry of Health, Labor, and Welfare (MHLW), a round table discussion by experts from rheumatology, dermatology, and pediatric medicine was conducted in multiple occasions. Methods: The definition of MCTD, and items included in the diagnostic criteria were generated by consensus method and evaluation using clinical data of typical and borderline cases of MCTD, by applying to the diagnostic criteria for MCTD proposed in 1996 and 2004 by the Research Committee of MHLW. Results: To the end, all committee members reached consensus. Then, the criteria were assessed in an independent validation cohort and tested against preexisting criteria. The revised criteria facilitate an understanding of the overall picture of this disease by describing the concept of MCTD, common manifestations, immunological manifestation and characteristic organ involvement. Conditions with characteristic organ involvement include pulmonary arterial hypertension, aseptic meningitis and trigeminal neuropathy. Even if the overlapping manifestations are absent, MCTD can be diagnosed based on the presence of the characteristic organ involvement. Furthermore, the criteria were validated for applicability in actual clinical cases, and public comments were solicited from the Japan College of Rheumatology and other associated societies. Conclusion: After being reviewed through public comments, the revised diagnostic criteria have been finalized.